Seismic retrofitting of corroded RC columns using advanced composite materials. (15th February 2019) - Rajput, Aditya Singh; Sharma, Umesh Kumar; Engineer, Kaizad
Highlights: Influence of corrosion was investigated on seismically deficient RC columns. Corrosion seems to have detrimental effects on the seismic behaviour of RC columns. HPFRC jacket and GFRP laminates were utilised to retrofit the corroded columns. Retrofitting using HPFRC jacket alone was found to recover full strength. Provision of GFRP wrapping further improved the seismic response of columns. Abstract: Investigations were undertaken to restore the seismic performance of corroded reinforced concrete (RC) columns. Six full-scale columns were cast and tested in this study. Four column specimens were corroded to a degree of corrosion of 30% using a pre-calibrated corrosion regime, while two columns were kept un-corroded. Out of the four corroded columns, three columns were retrofitted using different combinations of advanced composite materials. Retrofitting materials comprised of high-performance fibre reinforced concrete (HPFRC) and glass fibre reinforced polymer (GFRP) wraps. Performance of the column specimens was evaluated in terms of key strength and ductility indicators (displacement ductility, curvature ductility, and energy absorption). Two un-corroded columns consisted of one current code compliant well-confined column and another old age under-confined column. Corroded specimen when retrofitted with only HPFRC jacket yielded satisfactory recovery of strength and ductility in comparison to the un-corroded under-confined column but showed lower ductility when compared with seismically designed column specimen. Wrapping of GFRP laminates further improved the response of the specimens regarding strength and ductility parameters. Energy absorption was satisfactorily recovered for retrofitted columns. The moderately steep post-peak response was the only shortcomings of these retrofitting strategies.